Error Analysis In Writing Composition Recount TextMade By Freshmen Of English Department Ums In 2015/2016 Academic Year - Pratiwi, Anis Nur; , Prof. Dr. Endang Fauziati, M. Hum (2016)
ANIS NUR PRATIWI. A 320 120022. ERROR ANALYSIS IN WRITING COMPOSITION RECOUNT TEXT MADE BY FRESHMEN OF ENGLISH DEPARTMENT UMS IN 2015/2016 ACADEMIC YEAR The objectives of the study are to describe the types of error, the frequency type of error, dominant type of error and the sources of error made by freshmen of English Department UMS in 2015/2016 academic year. This study is qualitative research. The data are taken from all interlanguage errors which are made by the freshmen's writing composition recount text document. The technique for analyzing data are identifiying error, classifying of error, the describing of frequency, dominant of error, and the describing of sources of error. The results of this study has found the types of error in morphological, syntatical, and discourse combine in surface strategy. The frequency of each' types are morphological 17,34%, syntatical 79,83%, and discourse 12,5%. The most dominant types of error is syntatical type, its mean the freshmen lack knowledge in basic sentence pattern. These sources found interlingual transfer caused by interference of the learner's mother tongue and Intra lingual transfer is the negative transfer of item within the target language. Keyword: error analysis, freshmen, lingustic category, dominant